An environment-friendly solution for indoor air purification by using renewable photocatalysts in concrete: A review. (September 2016) - Nath, Ranjit K.; Zain, M.F.M.; Jamil, M.
Abstract: Photocatalyst is needed for cleaner environment and a better quality of life. This fact leads an idea of more eco-compatible use of light. This approach could become an integral component of strategies to reduce indoor air pollutants through the use of photocatalysts as construction materials. In this study, we discuss the quality of indoor air, sources of pollutants in the indoor environment, and the photocatalysis process. Moreover, the different parameters and uses of different photocatalysts in concrete for indoor air purification, starting from the early research until the current research, are described, and the reaction mechanism of photocatalytic oxidation and sustainable construction by using photocatalysts are also reviewed.